Delta Challenges under Nature-Based Solutions Perspectives - Zagare, Verónica; Sepulveda Carmona, Diego Andres (Journal of Delta Urbanism, 2022)
Deltaic areas and coasts tend to be extremely vulnerable as a result of the fusion of high-density urban agglomerations, overexploitation, and degradation of natural resources and the increase of climate events. The complexity of the combination of natural coastal and deltaic processes and human-made activities requires an integral perspective regarding planning, design, and governance (Meyer, 2009; Zagare, 2018).